ANALYSIS OF CAT CALLING BEHAVIOR OF HEGEMONIC MASCULINITY AND ITS HANDLING - Syalechya Amani Fatihah; Akhmad Harum; Aswar; Sultan Sahrir (Irfani, 2026)
This study aims to: (1) identify the forms and patterns of hegemonic masculinity-based catcalling behavior in the school environment; (2) analyze perpetrators' perceptions of catcalling and its impacts; (3) examine the psychological and social factors influencing both perpetrators and victims; and (4) explore intervention strategies through the Cognitive Behavioral Therapy (CBT) approach. This study employed a qualitative clinical case study design. The findings revealed that catcalling behaviors included whistling, comments on physical appearance, and sexually suggestive remarks, which resulted in social anxiety, fear, and avoidance of certain areas within the school environment. The identified behavioral patterns reflected body objectification, spatial dominance, collective action, and social intimidation as manifestations of hegemonic masculinity. Initially, perpetrators perceived catcalling as harmless joking, a means of gaining peer validation, expressing masculine superiority, and demonstrated limited empathy toward victims. The implementation of Cognitive Behavioral Therapy (CBT) promoted greater awareness of the consequences of such behavior, encouraged self-reflection, and improved cognitive and social responses among perpetrators. Preventive efforts were further supported through gender equality education and strengthened school regulations. The study concludes that catcalling represents a manifestation of hegemonic masculinity that reinforces gender inequality and therefore requires sustainable psychological interventions, educational programs, and school policy support